Estimation of Polarization and Spatial Parameters of a Radio Source Signal Using Triorthogonal Antenna - G. S. Gribov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Determination of the angular coordinates of the electromagnetic wave received from a radio source and estimating its parameters constitute the main tasks of radio monitoring. For direction finding of radio sources, classical amplitude, phase, and correlation methods are currently used. Amplitude methods involve the directional properties of the antenna. Phase and correlation methods are based on the difference in delays of signals received by spaced antenna elements. The information parameter in these methods consists in the phase front of the incident wave, which is orthogonal to the direction of its propagation. In this article, we consider a method for estimating the spatial parameters of a signal based on the orthogonality of the polarization plane relative to the propagation of a radio wave.Aim. Simulation of an algorithm for estimating the polarization and spatial parameters of a radio source signal based on the fixation of three projections of the electromagnetic field using a triorthogonal antenna system.Materials and methods. Mathematical simulation of an algorithm for spatial polarization processing of signals received by a triorthogonal antenna element in the MATLAB software environment.Results. The developed mathematical model of an algorithm for processing a spatially polarized signal received by a triorthogonal antenna system was used to obtain dependencies for assessing the polarization and spatial parameters of the received electromagnetic wave on the signal-to-noise ratio in the 50 kHz band. The obtained characteristics were used to determine the maximum standard deviations of the azimuth, elevation angle, ellipticity coefficient, and ellipse inclination. A comparison of the average level of energy loss of the received signal calculated by the spatial polarization algorithm and when receiving only the vertical component of the field, depending on the ellipticity coefficient and elevation angle, was carried out. As a result, spatial polarization processing allows a greater energy of the incoming signal to be employed, with the greatest gain being observed at elevation angles greater than 40°.Conclusion. The spatial polarization processing algorithm of three electromagnetic field projections makes it possible to estimate the spatial and polarization parameters of a propagating electromagnetic wave. Evaluation is possible provided that both field components – horizontal and vertical – are present in the signal. When determining the spatial and polarization parameters of the wave, the signal can be depolarized, thereby increasing its energy.